Comprehensive Physiology 2013
DOI: 10.1002/cphy.c120033
|View full text |Cite
|
Sign up to set email alerts
|

Muscle as a Secretory Organ

Abstract: Skeletal muscle is the largest organ in the body. Skeletal muscles are primarily characterized by their mechanical activity required for posture, movement, and breathing, which depends on muscle fiber contractions. However, skeletal muscle is not just a component in our locomotor system. Recent evidence has identified skeletal muscle as a secretory organ. We have suggested that cytokines and other peptides that are produced, expressed, and released by muscle fibers and exert either autocrine, paracrine, or end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
345
2
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(391 citation statements)
references
References 249 publications
8
345
2
19
Order By: Relevance
“…Physical exercise has been demonstrated to induce mitochondria biogenesis, upregulates skeletal muscle gene expression and protein synthesis, and increases skeletal muscle oxidative capacity both in older and sedentary populations [80] . Moreover, recent evidences promote the hypothesis of cross talk between muscle and different tissues mediated by cytokines and other peptides called myokines [81] which are involved both in acute exerciseinduced metabolic reactions, as well as in the longterm metabolic benefits induced by exercise [82] . Irisin is one of the most recently identified myokines.…”
Section: Beyond the Adipose Tissue Excess: The Importance Of Muscle Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical exercise has been demonstrated to induce mitochondria biogenesis, upregulates skeletal muscle gene expression and protein synthesis, and increases skeletal muscle oxidative capacity both in older and sedentary populations [80] . Moreover, recent evidences promote the hypothesis of cross talk between muscle and different tissues mediated by cytokines and other peptides called myokines [81] which are involved both in acute exerciseinduced metabolic reactions, as well as in the longterm metabolic benefits induced by exercise [82] . Irisin is one of the most recently identified myokines.…”
Section: Beyond the Adipose Tissue Excess: The Importance Of Muscle Mmentioning
confidence: 99%
“…Irisin may stimulate the transformation of white adipocytes into brite cells, thus suggested by a marked increase in the expression of uncoupling protein 1 (UCP-1). Adapted from Pedersen [82] .…”
Section: White Adipocytementioning
confidence: 99%
“…Flexibility exercise is one type of stretching exercise to improve the movements of muscles, joints, and ligaments (Siddiqui, Nessa & Hossain, 2010). Pedersen (2013), described that most of the exercise's benefits were mediated through the role of skeletal muscle. With the muscle contraction, myokines will be released, which promoting; the growth of new tissue, tissue repair, and multiple anti-inflammatory functions, which in turn reduce the risk of developing various inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Developing research has demonstrated that many of the benefits of exercise are mediated through the release of myokines which promote the growth of new tissue and reduces the risk of developing inflammatory diseases [4]. According to the World Health Organization, lack of physical activity contributes to approximately 17% of heart disease and diabetes, 12% of falls in the elderly and 10% of breast cancer and colon cancer [5].…”
Section: Introductionmentioning
confidence: 99%